Auditory processing and its cognitive correlates in older adults with mild cognitive impairment - Leelavathi Thamizhmani; Kanaka Ganapathy; Hari Prakash Palaniswamy; Arivudai Nambi Pitchaimuthu; Prabha Adhikari M. R. (BMC Geriatrics)
Abstract Introduction Age-related central auditory processing disorder (CAPD) is linked to cognitive decline in older adults, potentially preceding Mild Cognitive Impairment (MCI) by several years. While studies indicate that all auditory processing domains are impacted, it remains unclear which domain most significantly correlates with cognitive functions in MCI, warranting further investigation into these relationships. The current study investigated auditory processing deficits and their relationship with cognitive performance in older adults with MCI. Method The study recruited 70 participants aged 60 to 72 years, divided into two groups: MCI(n = 35) and healthy controls (n = 35) based on Montreal Cognitive Assessment scores. Comprehensive central auditory processing and cognitive assessments were done. Results The MCI group showed significant deficits across all auditory processing and cognitive domains. The enhanced right ear advantage in the dichotic test could be due to corpus callosum atrophy affecting left ear processing. Different factor structures in MCI suggest that they relied more on attentional resources for complex auditory tasks. Temporal processing tests showed high sensitivity in identifying MCI, with strong AUC and R² values, underscoring their clinical relevance. Conclusion Temporal processing deficits could serve as an early screening tool for cognitive decline in older adults. Larger studies targeting individuals with age-related hearing loss (ARHL) and MCI are essential, given the prevalence of ARHL in this population. Research should also examine the impact of tailored auditory training on cognitive function in MCI to inform interventions. Trial registration The study was registered in the Clinical Trials Registry of India (CTRI/2023/06/054277) on 21/06/2023 ( http://ctri.nic.in/ ).